Minimized Low-Profile Wideband Antennas Using High Impedance Surface - Yizhu Shen (International Journal of Antennas and Propagation)
This paper proposes minimized low-profile wideband antenna by employing high impedance surface (HIS), for wireless application scenarios at radio frequency, microwave, and even terahertz. To validate this concept with low cost and easy measurement, two prototypes at radio frequency are fabricated and tested. Firstly, antenna with dielectric-substrate reflector is proposed and analyzed and 4 × 6 HIS array is employed to minimize the antenna size to 0.57λL×0.86λL×0.078λL, while maintaining antenna performances such as bandwidth, gain, and directive radiation. Secondly, a substrate-less HIS is proposed to improve the antenna bandwidth from 36% to 52% and also reduces the antenna weight by 72%.